National Crime Victimization Survey: School Crime Supplement, 1995 ([Verlag nicht ermittelbar], 1998)
This supplement to the National Crime Victimization Surveys (formerly the National Crime Surveys) was designed to collect data on crime victimization in schools in the United States. Student respondents were asked a series of questions to determine their school attendance in the last six months. Other questions concerning schools were posed, including type of school, distance from home, and general attendance and monitoring policies. The data present information on the response of the school to student violation of rules, accessibility of drugs, and violence in school, including types of violence and student reaction. Other variables cover general violent crimes, personal larceny crimes, and household crimes and offer information on date, time, and place of crime. Demographic characteristics of household members such as age, sex, race, education, employment, median family income, and marital status are provided.